EFEKTIFITAS AROMATASE INHIBITOR YANG DIBERIKAN MELALUI PAKAN BUATAN TERHADAP SEX REVERSAL IKAN NILA MERAH Oreochromis sp. - YENNI PANCA LIANA (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2007)
Red tilapia, Oreochromis sp. is a popular fishery commodity because of the advantages such as easy at reproduction, fast growth and has a great taste. But in aquaculture, sometimes these advantages cause a problem to aquaculturist like uncontrolled reproduction. Monosex culture is a solution to face that problem by using sex reversal to male (masculinization). Commonly, sex reversal did by addition of 17-metiltestosteron hormone. But, since the material thought has carcinogenic effect and unfriendly to the environment, so then aromatase inhibitor can be an alternative. The aim of this research is to the effective dose of aromatase inhibitor added in pellet to sex reversal of red tilapia Oreochromis sp. The age of tested fishes are 9 to 13 days after hatching that are given fed treatment with synthetics food contained aromatase inhibitor in different doses (0 mg/kg, 500 mg/kg, 1000 mg/kg, 1500 mg/kg). The research methode a complete random design with 4 treatment and 3 repetitions. A hundred fish are put into 12 aquariums that are filled with 84 litres of water for 100 day periods. The fishes are ad libitum fed 4 times a day during the maintenance period. The use of aromatase inhibitor in sex reversal is able to produce male fishes fenotively. The highest percentage of the male occurred at dose 1500 mg/kg food, that are 78,625 %. Based on the test of variance informed that there is differences in the average of percentage male fishes produced from the 4 different treatments (0 mg/kg, 500 mg/kg, 1000 mg/kg, 1500 mg/kg). From the graphic, it can be seen that there is a pattern informs that the higher of the dose, the higher the average percentage of male fishes produced. Besides that, from the curve of respond between the average percentage male sex (Y) and dose of the aromatase inhibitor (X) result an accessment equation Y = 0,123X + 59,28. Aromatase inhibitor fed through the synthetic food to the Red Tilapia Oreochromis sp. is able to couse a masculinization. Based on the data gained, indicates that the higher the dose, the higher the average of male sex produced